Donative character of the good and a question of transcendence in the context of martin Heidegger’s thought - Korobczak, Paweł (Hybris, 2016)
In my paper I try to reconsider the character of the good. I show the specific structure of the good as “not-to-own-to-give”. Furthermore I investigate a possibility of such structure in Friedrich Nietzsche’s thought. On example of the bestowing virtue I show Nietzsche’s structure of donation as “to-own-to-give”. At the same time such structure of donation reveals problematic status of Nietzsche’s paradigm of absolute immanence. Then I show how transcendence as an „essence” of immanence constitutes Martin Heidegger’s main concept. He is very close to the structure of “not-to-own-to-give”, but the structure of “to-own-nothing” is still an ownership. It shows, anyway, that both Heidegger and Nietzsche have philosophized very close to the paradigm of the good. Eventually I show in Heidegger’s thought a possibility to go beyond his own paradigm that reveals possibility of the good as an infinite donation.